Structural and magnetotransport properties of bulk rare earth barium manganite and (la, pr)-ba-mn-o single-and bi-layer thin films - Wong, Jen Kuen (2011)
Magnetoresistance based sensor had been long used in magnetic field sensing application. Higher sensitivity and smaller in size is essential to keep up with the increasing of magnetic storage density. In this work, magnetotransport and magnetic properties of manganites are studied in both bulk and thin films. The influence of different rare earth cation in Ln site of bulk Ln0.67Ba0.33MnO3 (Ln= La, Ce, Pr, Nd, Sm, Gd, Dy and Er) compound synthesized via conventional solid state reaction route was studied. All substituted compound are in single phase except Ce, Dy and Er which are in oxide mixture due to differences in enthalpy of fusion. The crystal system undergoes transformation from orthorhombic to tetragonal when larger (La) cation was substituted by smaller (Gd) cation into Ln site. Substitution of smaller cation at Ln site increases the resistivity and shifts the phase transition temperature,TP and Curie temperature,TC to lower temperature. At room temperature, the ferromagnetic La0.67Ba0.33MnO3 (LBMO) undergoes magnetic dilution (glassy magnetic state) and became paramagnetic due to spin pinning effect when substituted by smaller rare earth cation. The highest room temperature negative %MR was given by Gd0.67Ba0.33MnO3 (GBMO) with -34.09% in 10kG. Substitution of smaller rare earth element into Ln site could enhance the %MR but results in the formation of complicated glassy magnetic state. The work then extended by fabrication of single and bi-layer (LBMO and/or PBMO) thin films through pulsed laser deposition technique on different type of substrate. Upon converted into thin film, the crystal systems remain orthorhombic. The unit cell of both LBMO and PBMO single layer thin films experience positive misfit due to lattice strain induced from lattice misfit between film and substrate. For bi-layer thin films, the lattice misfit is sequence dependent where negative misfit in PB/LB coupling and positive misfit in LB/PB coupling. The resistivity is higher for single layer thin film having more and larger nanocracks when deposited on substrate with smaller coefficient of thermal expansion. The resistivity of bi-layer thin films grown on amorphous substrate is lower than single layer thin films and is contrary on MgO substrate. TP shifted to lower temperature (<80K) in thin film form. The room temperature magnetic properties of single layer thin films were substrate dependent where PBMO growth on amorphous substrates was more ferromagnetic and vice versa for LBMO. However, room temperature magnetic properties between LB/PB and PB/LB bi-layer films are different. The magnetizations are relatively smaller as compared to single layer thin films (LBMO or PBMO) due to magnetic pinning effect. Their magnetization values were substrate dependent as well as stacking sequence on amorphous substrate but not for single crystal substrate. Typical polycrystalline manganites behavior was observed in all thin film samples where %MR further increase at lower temperature. This shows the extrinsic CMR behavior originated from grain boundary is stronger in thin films compared to bulk. Indeed, conversion from bulk to thin film can enhance %MR value. Single layer LBMO thin films growth on amorphous substrate shows low field magnetoresistance (LFMR) effect and further enhancement in bi-layer films but not on single crystal MgO substrate. Improvement of %MR value of -28.8% from bulk LBMO to -35.90% (LBMO-FS), -34.60% (LBMOCG)and -31.40% (LBMO-M) were observed at temperature of 80K in 10kG. The highest negative %MR and LFMR value obtained in this work was PBMO-M (-50.00%) and PB/LB-FS (-12.40%) at temperature of 80K in 10kG respectively whereas the highest room temperature negative %MR in 10kG was given by bulk GBMO (-34.09%)